People’s Support on Sin Tax to Finance UHC in Indonesia, 2016 - Thabrany, Hasbullah; Laborahima, Zahrina (UI Scholars Hub, 2016)
Indonesia has the highest prevalence of smokers with 67% of adult males were smokers. Smoking prevalence among all adults increased sharply from 27% in 1995 to 36.3% in 2013. High consumption of cigarettes has been correlated with low price and excise of cigarettes. Experiences from other countries showed that one of the most effective way to reduce cigarette consumption is by increasing cigarette price and excise. Burden of tobacco related diseases has increased. The health burden will increase claims of JKN or Universal Health Coverage which currently has claim ratio of 115% and the quality of care remain low. The difficulties in collecting contribution from non salaried workers are blamed to contribute the deficit. Many countries have earmarked cigarette excise to supplement financing of (UHC) both in tax-funded system or in social health insurance system. The question is do people support? This study explored the possibility the people’s support to increase cigarette prices and excise to meet financial shortage of the JKN.